Non-renewable but inexhaustible: Resources in an endogenous growth model - Martin Stürmer; Gregor Schwerhoff (Max Planck Institute for Research on Collective Goods, 2012)
This paper proposes an endogenous growth model with an essential non-renewable resource, where economic growth enables firms to invest in innovation in the extraction technology and to allocate more capital to resource extraction. Innovation in the extraction technology offsets the deterioration of ore qualities and keeps the production costs of the non-renewable resource constant. Aggregate output as well as production and use of the non-renewable resource increase exponentially. Our model explains the long-run trends of non-renewable resource prices and world production over more than 200 years. If historical trends in technological progress and in the deterioration of ore qualities continue, it is in the realm of possibility that non-renewable resources are de facto inexhaustible. Our results suggest that the industrialization in China and other emerging economies contributes to keeping non-renewable resource prices constant in the long run.
Keywords: O44; Q32; Q33; 330; Non-Renewable Resources; Endogenous Growth; Extraction Technology; Erschöpfbare Ressourcen; Bergtechnik; Endogener technischer Fortschritt; Neue Wachstumstheorie; Theorie